Copper and zinc ions govern the trans-directed dimerization of APP family members in multiple ways - August, Alexander; Schmidt, Nadine; Klingler, Johannes; Baumkötter, Frederik; Lechner, Marius; Klement, Jessica; Eggert, Simone; Vargas, Carolyn; Wild, Klemens; Keller, Sandro; Kins, Stefan (Journal of neurochemistry, 2019)
The amyloid precursor protein (APP) and its homologs amyloid precursor-like protein 1 (APLP1) and APLP2 have central physiological functions in transcellular adhesion that depend on copper and zinc mediated trans-directed dimerization of the extracellular domains E1 and E2. Copper binds to three distinct sites in APP, one in the copper binding (CuBD) and growth factor-like (GFLD) domains each within E1, and one in the E2 domain. For APLP1 and APLP2, metal binding has so far only been shown for the E2 domain. Zinc binding has been reported for all APP family members to a unique site in the E2 domain and an additional site essential for APLP1 E2 domain trans-dimerization. Using isothermal titration calorimetry, co-immunoprecipitation, and in vitro bead aggregation assays, we show that copper promotes cis- as well as trans-directed dimerization of APLP1 and APLP2, similar as reported previously for APP. Furthermore, we report a APP-specific zinc binding site with nanomolar affinity located in the E1 domain, whereas no binding of zinc to the individual subdomains GFLD or CuBD was detected. Zinc binding did not affect the cis- but trans-dimerization of APP and APLP1. Furthermore, zinc binding inhibited copper-induced trans-directed dimerization of APP. Together, we identified a high-affinity APP-specific zinc binding site in the E1 domain and revealed contrasting cis- and trans-directed dimerization properties of APP, APLP1, and APLP2 in dependence on zinc and copper ions. Consequently, changes in metal ion homeostasis, as reported in the context of synaptic activity and neurodegenerative diseases, appear as key modulators of homo- and heterotypic trans-cellular APP/APLPs complexes.